Novel nickel–cobalt phosphite with face-sharing octahedra derived electrocatalyst for efficient water splitting. Issue 8 (19th June 2019) - Wu, Jian; Lin, Lingling; Morvan, Francois J.; Du, Juan; Fan, Weibin
Abstract : Nickel–cobalt phosphite (CoNiPO) including local structural motifs with face-sharing octahedra shows excellent OER activity. The derivatized electrocatalyst (NiP2 @CoNiPO) exhibits high HER activity. DFT calculations indicated the super-exchange effect in CoNiPO can adjust local electronic structure and improve their catalytic activity. Abstract : The local electronic structure of a transition metal can be adjusted by changing the metal octahedral linking mode in order to control its electrocatalytic activity. Perovskite (corner-sharing octahedra) and layered hydroxide (edge-sharing octahedra) structures have previously been studied as OER electrocatalysts. However, catalysts with face-sharing octahedra have still rarely been studied to date. In this work, a nickel–cobalt phosphite including local structural motifs with face-sharing octahedra has been studied as a model electrocatalyst for OER. The optimized cobalt nickel phosphite (CoNiPO) shows excellent OER activity with a small overpotential of 320 mV, as well as high stability. DFT theoretical studies show that the super exchange effect of Co–O–Ni in CoNiPO can effectively adjust its local electronic structure and improve the OER catalytic activity. To overcome the low HER catalytic activity of CoNiPO, the catalyst is prepared via further phosphorization, forming Ni2 P@CoNiPO, which exhibits high HER catalytic activity. Moreover, CoNiPO and Ni2 P@CoNiPO coupled together shows excellent activity and long-term catalytic stability towards overall water splitting. Our findings will be a promising pathway to studying the relationship between local structural motifs with face-sharing octahedra and catalytic properties.